Interaksi Sosial terhadap Anak Berkebutuhan Khusus (Inklusi) di Madrasah Ibtidaiyah Persmin dan Raden Rahmat Wonokromo Surabaya - Muis, Muhammad; Tubayanah, Komsatun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This type of research is field research which is carried out using a qualitative approach, namely an approach that places more emphasis on the analysis of the inductive inference process and analysis of the dynamics of the relationship between the observed phenomena, using logic, with a Qualitative Descriptive approach. Research subjects at the Persmin and Raden Rahmat Wonokromo Madrasah Surabaya. Triangulation techniques to test the credibility of the data were carried out by checking the data against the same source with different techniques. The problem at basic education institutions or madrasah ibtidaiyah in Wonokromo sub-district is that there are no special programs for inclusion or special needs at these schools, these two educational institutions experience difficulties in interacting and teaching in learning the material presented. The research results show that the role of teachers and peers is to support and help each other in interacting well and collaborating with children with special needs and normal children during the learning process. The assimilation process takes the form of efforts to eliminate differences, help and respect children with special needs during the learning process and provide comfort and learning motivation that can be accepted by children with special needs.